Características del análisis proximal de harinas obtenidas de frutos de plátanos variedades papocho y pelipita (musa abb simmonds) (2013)
Untreated raw flours obtained from fruits of non-commercial plantain varieties Papocho and Pelipita (Musa ABB Simmonds) at different stages of development were subjected to proximate analysis and its possible use as food raw material potential was analyzed. Comparative results showed that the contents and percentages of crude fiber in Papocho varied from 2.54 to 1.37% and Pelipita between 6.45 and 0.88%, crude protein in Papocho between 6.70 and 3.81% and Pelipita between 2.74 and 1.89%, ash in Papocho between 3.66 and 2.41% and Pelipita between 2.43 and 2.10%, and were affected (P and lt; 0.05) by the stage of fruit development; while plantain variety affected fat contents in Papocho between 0.64 and 0.48% and Pelipita between 0.55 and 0.35% in both flour samples. In Pelipita variety a low moisture content (9.85%) was found and the highest total carbohydrate content (85.86%) registered at 77 days after flowering.